2008
DOI: 10.1002/ibd.20543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutamine on proinflammatory gene expression and activation of nuclear factor kappa B and signal transducers and activators of transcription in TNBS-induced colitis

Abstract: Inhibition of the expression of proinflammatory mediators that are regulated by the NF-kappaB and STAT signaling pathways contribute to the therapeutical effect of glutamine in the TNBS model of experimental colitis. These effects may be brought about by inhibition of oxidative stress and reduced expression of proinflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 63 publications
8
96
0
3
Order By: Relevance
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 78%
“…35,46 The action of glutamine on cytokine production is mediated by different signaling pathways (Fig. 2), including nuclear factor kappa B (NF-jB), 16,46,47,50,51 signal transducer and activator of transcription (STAT), 37,47 Jun N-terminal kinase (JNK), 48 or peroxisome proliferator-activated receptor-c (PPARc). 49 During IBD, oxidative stress is increased in intestinal mucosa and antioxidative defenses, especially glutathione, are reduced.…”
Section: Glutaminementioning
confidence: 99%
“…After washing with Trisbuffered saline containing 0.05% Tween 20, the membranes were incubated for 1 hour at room temperature with secondary horseradish peroxidaseconjugated antibody (1:5000; Dako, Glostrup, Denmark), and visualized using enhanced chemiluminescence (ECL) detection kit (Amersham Pharmacia, Uppsala, Sweden). 27 The density of the specific bands was quantified with an imaging densitometer (Scion Image J Software 1.46a, Bethesda, Maryland).…”
Section: Real-time Reverse Transcription-polymerase Chainmentioning
confidence: 99%